2016
DOI: 10.1038/bjc.2016.373
|View full text |Cite
|
Sign up to set email alerts
|

In utero exposure to radiation and haematological malignancies: pooled analysis of Southern Urals cohorts

Abstract: Background:It is scientifically uncertain whether in utero exposure to low-dose ionising radiation increases the lifetime risk of haematological malignancies.Methods:We pooled two cohorts from the Southern Urals comprising offspring of female workers of a large nuclear facility (the Mayak Production Association) and of women living in areas along the Techa River contaminated by nuclear accidents/waste from the same facility, with detailed dosimetry.Results:The combined cohort totalled 19 536 subjects with 700 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…No association was found in mortality-based analyses. 118 Consistent with findings from the Mayak Nuclear Facility studies, Draper et al 119 also demonstrated that paternal preconception irradiation did not cause childhood leukemia and non-Hodgkin lymphoma in the offspring of radiation workers in United Kingdom.…”
Section: Nuclear Worker Cohortsmentioning
confidence: 66%
See 1 more Smart Citation
“…No association was found in mortality-based analyses. 118 Consistent with findings from the Mayak Nuclear Facility studies, Draper et al 119 also demonstrated that paternal preconception irradiation did not cause childhood leukemia and non-Hodgkin lymphoma in the offspring of radiation workers in United Kingdom.…”
Section: Nuclear Worker Cohortsmentioning
confidence: 66%
“…A dose–response relationship between α-radiation exposure and incidence of various cancerous and noncancerous disorders was observed in nuclear workers chronically exposed by inhalation to plutonium ( 239 Pu) in the Mayak Nuclear Enterprise (Chelyabinsk region, Russia). 98 - 120 For instance, the incidence of lung cancer corrected for smoking was 0.56, 0.59, and 0.83 at body burdens of 343, 1180, and 4200 Bq, respectively, in 500 nuclear workers relative to internal controls. Of note, the lung cancer incidence was linearly associated with cigarette smoking, with 2-fold risk of lung cancer in those workers who smoked 1 pack of cigarettes per day for at least 5 years.…”
Section: Nuclear Worker Cohortsmentioning
confidence: 99%
“…Both studies found no sex difference in radiation risk. The Urals Prenatally Exposed Cohort (UPEC) (i.e., in utero exposed members of Techa River and Mayak cohort combined and exposed chronically, mean estimated dose in utero: 14.1 mGy) showed no increased risks of incidence (RR/10 mGy of in utero dose = 0.99, 95% CI: 0.96-1.01) or mortality (RR/10 mGy of in utero dose = 0.98, 95% CI: 0.94-1.01) for adulthood solid cancer (the mean age among alive subjects at the end of follow up: 53 years) [5] and no increased risks of incidence or mortality for hematological malignancy (mean age among alive subjects at the end of follow up: 51 years) [6]. The authors of the UPEC study considered a limited number of cases because of the young age of the cohort and thus limited ability to estimate cancer risks.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation has been recognized to increase the risks of mortality (followed-up through age of 46 years) [1] and incidence of adult-onset solid cancer (followed-up through age of 55 years) in individuals who were acutely exposed to atomic bomb radiation in utero in Hiroshima and Nagasaki, Japan [2][3][4]. However, the studies of those chronically exposed in utero in the Southern Urals of Russia, residents of communities near the contaminated Techa River and offspring of Mayak nuclear workers, did not show increased risks of incidence and mortality for solid cancer [5] and no increased risks of incidence or mortality for hematological malignancy in adulthood [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, longitudinal data collection has subsequently identified significant associations between in utero exposure and increased cancer risk . A study of 19 536 children born to women either employed in a large nuclear facility in the Southern Urals or living in areas near the Techa river, which was contaminated by waste from the same nuclear facility, demonstrated an increase in haematological malignancies in children whose mothers had been exposed to more than 80 mGy ionising radiation while in utero (n = 58, excess relative risk of 1.27, 95% confidence interval [CI] 0.02–2.56) . Importantly, fetal exposure to ionising radiation during diagnostic examinations is at a far lower magnitude than fetal survivors who were exposed in Hiroshima and Nagasaki.…”
Section: Ionising Radiationmentioning
confidence: 99%